2018
DOI: 10.1186/s13567-018-0519-9
|View full text |Cite
|
Sign up to set email alerts
|

Binding determinants in the interplay between porcine aminopeptidase N and enterotoxigenic Escherichia coli F4 fimbriae

Abstract: The binding of F4+ enterotoxigenic Escherichia coli (ETEC) and the specific receptor on porcine intestinal epithelial cells is the initial step in F4+ ETEC infection. Porcine aminopeptidase N (APN) is a newly discovered receptor for F4 fimbriae that binds directly to FaeG adhesin, which is the major subunit of the F4 fimbriae variants F4ab, F4ac, and F4ad. We used overlapping peptide assays to map the APN-FaeG binding sites, which has facilitated in the identifying the APN-binding amino acids that are located … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 37 publications
(48 reference statements)
0
6
0
Order By: Relevance
“…As we know, F4ac infections mostly occur in the piglets with the presence of F4ac receptors, and porcine aminopeptidase N (APN) is a newly found F4ac fimbrial receptor in our and other labs' previous studies (Melkebeek et al 2012;Xia et al 2018a). In the later experiment, we proved that the amino acids 149-161, 176-188, and 200-218 are the determinant epitopes for F4ac FaeG to interact with APN directly, and further determined N209 and L212 are the critical sites of F4ac FaeG in binding to the jejunum of piglets (Xia et al 2018a(Xia et al , 2016. That is to say, FaeG is the target for receptor recognition and can control receptor-mediated binding capacity as well.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…As we know, F4ac infections mostly occur in the piglets with the presence of F4ac receptors, and porcine aminopeptidase N (APN) is a newly found F4ac fimbrial receptor in our and other labs' previous studies (Melkebeek et al 2012;Xia et al 2018a). In the later experiment, we proved that the amino acids 149-161, 176-188, and 200-218 are the determinant epitopes for F4ac FaeG to interact with APN directly, and further determined N209 and L212 are the critical sites of F4ac FaeG in binding to the jejunum of piglets (Xia et al 2018a(Xia et al , 2016. That is to say, FaeG is the target for receptor recognition and can control receptor-mediated binding capacity as well.…”
Section: Discussionmentioning
confidence: 96%
“…Nine of 25-day-old Landrace and Large White 2-way crossbred Pigs were screened according to our previous studies (Xia et al 2018a , 2015a ). These piglets are susceptible to F4ac + E. coli and randomized into three groups: the control group without ETEC infection, F4ac infected group and F4acΔ faeG infected group.…”
Section: Methodsmentioning
confidence: 99%
“…Based on our in vitro results, we can infer that the ZnuACB system contributes in colonizing ETEC C83902 in a zinc-limited gut. Our previous research has shown that FaeG, the major subunit of F4 fimbriae, can bind to the specific porcine aminopeptidase N (APN) receptor and tightly adheres to the porcine cell lines of the IPEC-J2 cell [ 38 ]. This means that FaeG is the most important and direct factor to evaluate the adherence ability for F4 E. coli .…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, we observed that APN directly interacted with the major FaeG subunit of F4 fimbriae and affected F4 bacterial adherence to host cells [92]. The binding determinants of the APN-FaeG interaction contain residues important for zinc binding, and in a certain concentration range, the change in Zn 2+ concentrations affects the biological activity of the APN protein as well as the adherence between E. coli F4 and host intestinal epithelial cells [90,93]. In addition to cleaving N-terminal amino acids from small oligopeptides on the apical surface of intestinal epithelial cells, APN participates in regulating the MAPK/ ERK1/2 signalling pathway in monocytes, while its zincbinding site is blocked by inhibitory antibodies [91,94].…”
Section: Zinc Affects the Activity Of Host Receptors And Immune Respomentioning
confidence: 99%